Performance analysis of HAPS-based relaying for hybrid FSO/RF downlink satellite communication - Swaminathan, Ramabadran (2020)
Free space optics (FSO) communication has garnered significant importance to provide gigabit capacity links owing to its unique features. However, its performance is limited by the adverse effects of transmission medium such as atmospheric turbulence induced fading, wind, etc. Therefore, it is wise to backup with reliable radio frequency (RF) links to improve the performance of FSO communication. The fusion of FSO and RF technologies is a suitable candidate for future satellite communication (SATCOM) systems. In this context, the present paper proposes a novel system model for High-Altitude Pseudo-Satellite (HAPS)-based relaying for downlink scenario utilizing both FSO and RF links. The performance of the proposed hybrid FSO/RF SATCOM system is investigated through average and asymptotic symbol error probability (SEP) analyses. Further, the obtained closed-form expressions for average SEP are validated using Monte-Carlo simulation results.